Pregnancy outcome in women with early pregnancy bleeding in a tertiary health care facility in Southwestern, Nigeria - Awolola Olalekan Olugbenga (Wolters Kluwer Medknow Publications, 2019)
Background: Bleeding in early pregnancy is a common occurrence, but very little is known about the outcome of pregnancy complicated by bleeding during the early part of the gestation. This prompted me to explore these in a prospective cohort study over a period of 12 months. Objectives: The aim of this study is to determine the mode of presentation and the materno-fetal outcome in pregnancies complicated by early pregnancy bleeding and compare with a group without such complication. Materials and Methods: A total of 72 cases were observed and these patients were matched with a control group in maternal age in years (+2), parity and gestational ages in weeks. Thus, a total number of 144 patients were studied. Results: Pregnancy loses or abortions occurred in 12 patients (16.6%) in the study group compared with 3 patients (4.1%) in the control group (P < 0.05), 14 patients (19.4%) had preterm deliveries in the study group, compared with four patients (5.5%) in the control group (P < 0.05) and low birth weight was observed in 15 patients (20.83%) among the study group compared with 5 patients (6.94%) in the control group (P < 0.05). All the three outcome measures above had statistically significant differences when compared in between the two groups. These poor outcomes were observed among those who bled in the second trimester, those who had episodes of bleeding in both the first and the second trimesters or recurrent vaginal bleeding throughout the pregnancy. Conclusion: The outcome of this study showed that bleeding in early pregnancy, especially during the second trimester or recurrent bleeding in both the first and the second trimesters correlates with poor pregnancy outcomes.